1993
DOI: 10.1111/j.1471-0528.1993.tb15212.x
|View full text |Cite
|
Sign up to set email alerts
|

Type III collagen content in the skin of postmenopausal women receiving oestradiol and testosterone implants

Abstract: Objective To investigate the effect of subcutaneous oestradiol and testosterone on the proportion of type III collagen in the skin of postmenopausal women. Design A cross sectional comparison. Setting Dulwich Hospital menopause clinic. Subjects Fourteen untreated women and 11 women who had received subcutaneous oestradiol and testosterone for a median 8.0 years (range 3–14). Ten of the untreated women received subcutaneous hormone implants and the effect on skin collagen was studied pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
3
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 14 publications
(18 reference statements)
1
40
3
3
Order By: Relevance
“…Our findings are surprising; previous uncontrolled studies report higher levels of skin collagen when postmenopausal women take hormone replacement treatment for two to 10 years 15 , this could be occurring secondary to increased collagen synthesis 16 or inhibition of collagen loss 17 . Our study, analysing vaginal tissue, has shown the converse over a six-month treatment interval, with a significant drop in total vaginal collagen occurring after oestrogen therapy.…”
Section: Discussioncontrasting
confidence: 53%
“…Our findings are surprising; previous uncontrolled studies report higher levels of skin collagen when postmenopausal women take hormone replacement treatment for two to 10 years 15 , this could be occurring secondary to increased collagen synthesis 16 or inhibition of collagen loss 17 . Our study, analysing vaginal tissue, has shown the converse over a six-month treatment interval, with a significant drop in total vaginal collagen occurring after oestrogen therapy.…”
Section: Discussioncontrasting
confidence: 53%
“…A randomized, double-blind, placebo-controlled trial carried out by Sauerbonn et al (2000) demonstrated an increase of 6.49% in skin collagen fi ber content after six months of treatment with an oral combination of estrogen and cytoproterone acetate. Other authors have demonstrated an increase in overall collagen content (Brincat et al 1987) and specifi cally collagen type III (Savvas et al 1993;Schmidt et al 1996). Another study found no difference in skin thickness or collagen content in upper arm or abdominal skin following oral estrogen therapy (Haapasaari et al 1997); however the patients in this study had only a short period of estrogen defi ciency (median time post-menopause 12 months), which may explain this fi nding.…”
Section: Hormone Replacement Therapycontrasting
confidence: 47%
“…The role of estrogen in collagen metabolism in POP As estrogen deficiency is a known risk factor for POP [65], estrogen replacement therapy traditionally has been used to improve structural integrity of the pelvic tissue with favourable effects on urinary incontinence [66][67][68][69]. Previously, estrogen receptors (ER) were identified in the nuclei of connective tissue and of the smooth muscle cells of the bladder trigone, urethra, vaginal mucosa, levator ani stromal and uterosacral ligament.…”
Section: The Fibroblast In Popmentioning
confidence: 99%